Respuesta :
Answer:
C. 42.
Step-by-step explanation:
This is an arithmetic sequence with common difference d = 4 and first term a = -3.
Sum of n terms = (n/2)[2a + (n - 1)d]
Sum of six terms = (6/2)[2(-3) + (6 - 1)4]
= 3 * (-6 + 20)
= 42.
Answer:
C) 42
Step-by-step explanation:
Given is an Arithmetic Sequence, where
First term a = - 3
Common Difference d = 1-(-3)= 4
n = 6
[tex]S_6=? \\ \\ \because \: S_n = \frac{n}{2} \{2a + (n - 1)d \} \\ \\ \therefore \: S_6 = \frac{6}{2} \{2 \times ( - 3) + (6 - 1)4 \} \\ \\ \therefore \: S_6 = 3 \{ - 6 + 20\} \\ \\ \therefore \: S_6 = 3 \times 14 \\ \\ \huge \red{ \boxed{ \therefore \: S_6 = 42}}[/tex]